2016
DOI: 10.1051/matecconf/20166600045
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Review on Sustainable Leadership (SL)

Abstract: Leadership has been identified as one of the factor contributes to construction organisation success. Therefore, leadership has acts as an admixture to the sum of leader's effort and subordinates teamwork in order to accomplish organisational goals. There are several types of leadership style that have been practiced by leaders in the construction industry, however, there are still several morality issues such as corruptions, mismanagement and spillages occurred among leaders in the industry. Therefore, a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Regarding construction organisations, it has been observed that leadership play a strategic role towards their success (Zulkiffli & Ahmad, 2016). Nevertheless, Zulkiffli and Ahmad pointed out the moral issues that have tended to restrain performance in the building industry.…”
Section: Leadership Training In the Building Industry In Kenyamentioning
confidence: 99%
“…Regarding construction organisations, it has been observed that leadership play a strategic role towards their success (Zulkiffli & Ahmad, 2016). Nevertheless, Zulkiffli and Ahmad pointed out the moral issues that have tended to restrain performance in the building industry.…”
Section: Leadership Training In the Building Industry In Kenyamentioning
confidence: 99%
“…Assessing and raising the awareness of the principles of sustainability of RL is by considering responsibility towards individual, groups, and organisations, as well as the personal level of leaders involved in the transformational process. According to Zulkiffli and Latiffi in (2016), they defined SL as "an ability to influence and motivate individual, groups, organisation and society by assessing sustainability knowledge into their principles without neglecting experience from the past, so that it can be improved continuously either in present also in future". (Zulkiffli & Latiffi, 2016, p. 2).…”
Section: Sustainable Leadership (Sl)mentioning
confidence: 99%
“…A sustainable leadership (SL) strategy depends on an organisation that is flexible and adaptive to change with the goal of creating value for shareholders and society and is a holistic approach to business management (McCann and Holt, 2010;Zulkiffli and Latiffi 2016). SL considers the connection among business, society, and environment, and value is created on the basis of long-term strategic decision-making (Iqbal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%